PERMIT PROCEDURE OF ESTHABLISMENT AND SUPERVISION OF NURSING CLINIC IN BANTUL REGENCY - Nasrullah, Nasrullah; Alfarisyi, Mishbahul Huda (Jurnal Media Hukum, 2012)
As one of the health professions, nurse normally does no have independent authority to conduct medical practice. However, according to several regulations, nurse has a chance to establish and run his/her own nursing clinic. So far, there are six individual nursing clinics have been operated in Bantul Regency. By utilizing empirical research method with legislation approach, this research aims at finding out the importance and the permit procedure to establish nursing clinic as well as to know the supervision means used by the government upon the operated nursing clinic in Bantul Regency. This research proved that nursing clinics have given beneficial advantages on the society as whole. Meanwhile, to operate a nursing clinic a nurse has to be granted a Nursing Practice Permit Letter (Surat Izin Praktik Perawat/SIPP) from the government. Finally, the nursing clinic is supervised by the Health Bureau by means of supervision and control program.Keywords: nursing practice, nursing clinic, Nursing Practice Permit Letter, supervision and control program